Imaginative Machines. - Romele, Alberto (Techné: Research in Philosophy & Technology, 2018)
In philosophy of emerging media, several scholars have insisted on the fact that the "new" of new technologies does not have much to do with communication, but rather with the exponential growth of recording. In this paper, instead, the thesis advanced is that digital technologies do not concern memory, but imagination, and more precisely, what philosophers from Kant onwards have called productive imagination. In this paper, however, the main reference will not be Kant, but Paul Ricoeur, who explicitly refers to the Kantian productive imagination in his works, but also offered an externalized, semioticized, and historicized interpretation of it. The article is developed in three steps. In the first section, it deals with Ricoeur's theory of narrative, based on the notions of mimesis and mythos. In the second section, it is first argued that human imagination is always-already extended. Second, it will be shown how mimesis and mythos are precisely the way software works. In the third section, the specificity of big data is introduced. Big data is the promise of giving our actions and existences a meaning that we are incapable of perceiving, for lack of sensibility (i.e., data) and understanding (i.e., algorithms). Scholars have used the Foucauldian concepts of panopticon and confession for describing the human condition in the digital age. In the conclusion, it is argued that big data makes any form of disclosure unnecessary. Big data is an ensemble of technological artifacts, methods, techniques, practices, institutions, and forms of knowledge aiming at taking over the way someone narratively accounts for himself or herself before the others. Hence, another Foucauldian notion is representative of this age: the parrhesia, to speak candidly, and to take a risk in speaking the truth, insofar as such a possibility is anesthetized.